The crime of breaching the duties of a policeman during armed clan conflicts(in Iraqi legislation) - Mezal Ghanem Fayad , Fouad; Hanoun Khalaf Al-Daraji , Prof. Dr. Ghazi (Basra studies journal, 2022)
The duty to prevent and suppress the commission of crimes is one of the important duties entrusted to the policeman in the field of security. There is no doubt that the crimes of armed clan conflicts fall within the responsibility of the policeman and are determined by them when they occur within the constraints of their security responsibility, and what emanates from the danger of these conflicts, whether they are immediate and unorganized or an organization. It is called a tribal tradition (the clan bench). Next, the judiciary has dealt with this type of crime as having a terrorist nature. The investigation into the crime of violating the duties of a policeman during armed tribal conflicts is a correction of police action within the general framework of the security function in maintaining security, public order, spreading reassurance within the community, and preventing attacks that may occur from one to another. It was also searched to verify the responsibility of the policeman for violating his duties in the event of their fulfillment in accordance with the general principles in the amended Iraqi Penal Code No. (111) for the year 1969, and the appropriateness of the principles in terms of shedding the same criminalization tools after making legislative amendments to the criminal models of Article (331) penalties. And the penalties for the Iraqi Internal Security Forces No. (14) of 2008, as amended in Article (27) of it. The criminal responsibility of the policeman during these crimes is achieved in violating orders or violating the prevention of their commission, since the duties of the policeman in preventing, combating and preventing crimes are carried out in the framework of legitimacy, the rule of law, and accountability when deviating from it or not complying with its implementation.